Quantification of VOC emissions from paint spraying on a construction site using solid phase microextraction devices. Issue 12 (15th October 2017) - Cheng, Wen-Hsi; Huang, Hsiao-Lin; Chen, Kang-Shin; Chang, Yu-Jen
ABSTRACT: The objective of this study was to measure the emission of, and personal exposure to workers, volatile organic compound (VOC) during paint spraying on a construction site. Needle trap samplers (NTSs), which are a green solid phase microextraction sampling technology, were used to obtain air samples at a large music exhibition center. The standard active sampling method using charcoal tubes and a personal air pump, Method 1501, was simultaneously utilized at the sampling sites to assess the workers' VOC exposures. Analysis of the data thus obtained showed that benzene, toluene, ethylenebenzene, and xylenes (BTEXs) were the main emission compounds. Acetone and isobutyl alcohol, which are used as thinning solvents, were detected as minor emission compounds. The emitted concentrations of most compounds were lower than the legal emission limits in Taiwan except that of benzene, for which the 2-ppm time weighted average short-term exposure limit was exceeded. The packed divinylbenzene (DVB) in the NTS was observed under an environmental scanning electron microscope, and many fine aerosols were found to be deposited on the surface of the DVB adsorbents, causing VOC extraction efficiencies after the fifth sampling in the field to decline. Workers on construction sites should be protected from emissions of VOC and fine particulates to preserve their occupational health.